Meeting Abstracts of the 3rd Uludag Cardiology Summit, March 16-19, 2023, Bursa, Turkey - 3rd Uludag Cardiology Summit (The European Research Journal, 2023)
Rare Side Effect Of Lorlatinip: Complete AV Block. Removal of Broken Guidewire in the Coronary Artery During Coronary Angiography. Is There a Relationship Between Deep Venous Thrombosis and Hemoglobin/Erythrocyte Distribution Width Ratio in Patients with Acute Pulmonary Embolism? Arrhythmia Predictive ECG Parameters in Takayasu Arteritis Patients. The Effect of Uric Acid/Albumin Ratio on GRACE Prognostic Score in NSTEMI Patients. Effects of Levosimendan Use on High Sensitivity C-Reactive Protein (Hs-CRP) in Decompensated Heart Failure Patients. Mechanical Dispersion Assessed by Speckle Tracking Echocardiography Predicts Appropriate Implantable Cardioverter Defibrillator Therapy in Patients with Ischemic and Non-Ischemic Cardiomyopathy. Acute Symptomatic Hyponatremia Following Coronary Angiography. Subacute Anterior Myocardial Infarction After Bonsai Use. Alternative to High-Risk Surgery: Main Coronary Stenting and Triple Balloon. The Relationship Between Non-Dipper Hypertension and Visceral Adipose Index in Newly Diagnosed Hypertensive Patients. Biological Heart Valves Versus Mechanical Heart Valves With Low-Dose Warfarin During Pregnancy. The Role of Flow-Mediated Dilation Test in Displaying Subclinic Atherosclerosis in Patients With Obstructive Sleep Apnea Syndrome. Evaluation of Embolism Risk in Aortic Valve Endocarditis Case With 2D TEE and 3D TEE. Assessing Arrhythmia Risk in COVID-19 Patients by Microvolt T Wave Alternance and Heart Rate Variability. The Effect of Hypomagnesemia on Hospitalization in Preserved Ejection Fraction Heart Failure Patients. The Effect of Left Atrial Appendage Function on Mitral Restenosis After Percutaneous Mitral Balloon Valvuloplasty. Mitral Stenosis and Giant Left Atrial Thrombosis. A Comprehensive Network Meta-Analysis: Comparison of Long-Term Outcomes Between Intravascular Ultrasound, Optical Coherence Tomography, and Angiography-Guided Stent Implantation. The Relationship Between Mortality and Sytemic Inflammatory Response Index in Patients With ST-Elevation Myocardial Infarction Undergoing Percutaneous Intervention. Fluoroscopy-Assisted Coronary Volume Ratio-Derived Index of Microvascular Resistance in Patients With Intermediate Coronary Stenosis. Safety and Efficacy Results of Percutaneous Renal Stent Implantation in Patients With Acute Coronary Syndrome With Ectatic and Aneurysmatic Coronary Arteries. Comparison of Simplified Echocardiographic Pulmonary Arterial Pulsatility Index Measurement With Invasive Values in The Evaluation of Right Ventricular Functions in Patients With Pulmonary Arterial Hypertension. The Relationship of Renal Function With Carotid Atherosclerosis According to Retinopathy Presence in Patients With Tip 2 Diabetes Mellitus. A New Marker of Coronary Collateral Flow in Patients Presenting With Acute Myocardial Infarction. The Independent Relationship Between Ankylosing Spondilitis and Aortic Stiffness Index. The Relationship Between Vitamin-D Deficiency and CAVI in Hypertensive Patients. Effects of Sarcopenia on in-Hospital Results and Mid-Term Follow-Up in Patients With Coronary Artery Disease and COVID-19. Complex Primary Percutaneous Intervention of The Left Main Coronary in a Patient With Cardiogenic Shock: Tri-Kissing PTCA. Is There a Relationship Between Plasma Atherogenic Index and Coronary Flow Reserve in Patients With Ankylosing Spondylitis? Heart Rate Variability of Acute Ischemic Stroke Patients According to Troponin Levels. In Stable Angina Pectoris Patients Performed Coronary Angiography, Syntax 1 Score is Associated With Left Atrial Volume Index Increase, Independently of Left Ventricular Structure and Functions. Evaluation of the Left Heart Mechanics by Two- Dimensional Speckle Tracking Echocardiography in Adult Group of Celiac Disease Patients. Recurrent Ischemic Stroke Due to Postpartum Intracardiac Thrombus in Buerger’s Disease. Usefulness of C-Reactive Protein Albumin Ratio and 30 Days Major Adverse Cardiovascular Events in Patients With Acute Lower Limb İschemia. Outcomes of Octogenarians Undergoing Percutaneous Coronary Intervention Due to Acute Coronary Syndrome. The Impact of Thrombus Aspiration on in-Hospital and Long-Term Mortality in Patients With ST-Elevation Myocardial Infarction Who Underwent Primary Percutaneous Coronary Intervention. The Relationship Between Mitral Annular Calcification and The Triglyceride/Glucose Index. The Relationship Between TIMI Frame Rate and Eosinophil Count, Eosinophil-Leukocyte Ratio and Eosinophil-Lymphocyte Ratio in ST Elevation Myocardial Infarction. A Young Case With Acute Inferior Myocardial Infarction as a Late Complication of Previous Anterior Myocardial Infarction. Invasive Cardiologist Nightmare: Coronary Ectasia and Acute Coronary Syndrome Coexistence.